Use of 18F-NaF PET in the staging of skeletal metastases of newly diagnosed, high-risk prostate cancer patients: a nationwide cohort study - Christian Torp-Pedersen; Mette Nørgaard; Helle D Zacho; Lars J Petersen; Anna Winther Mogensen; Marie T Pank (BMJ Open)
Objective To determine whether preoperative staging of high-risk prostate cancer with 18F-sodium-fluoride (18F-NaF) positron emission tomography (PET) reduces the risk of skeletal metastases.Design Nationwide, population-based cohort study using real-world data.Setting The study used national health registries, including all sites in Denmark from 2011 to 2018.Participants Newly diagnosed high-risk prostate cancer patients who underwent radical prostatectomy from 2011 to 2018. Patients were stratified into two groups according to the preoperative imaging modality of either 18F-NaF PET or bone scintigraphy.Main outcome measures The risk of skeletal-related events (SREs) as a proxy for skeletal metastases following radical prostatectomy. The secondary endpoint was overall survival.Results Between 1 January 2011 and 31 December 2018, 4183 high-risk patients underwent radical prostatectomy. Of these patients, 807 (19.3%) underwent 18F-NaF PET and 2161 (51.7%) underwent bone scintigraphy. The remaining 30% were examined by a different imaging method or did not undergo imaging. Using the inverse probability of treatment weighting to control potential confounding, the HR of experiencing an SRE for patients in the 18F-NaF PET group versus the bone scintigraphy group was 1.15 (95% CI 0.86 to 1.54). The 3-year survival rates were 97.4% (95% CI 96.1 to 98.7) and 97.1% (95% CI 96.4 to 97.9) for patients receiving 18F-NaF PET and bone scintigraphy, respectively.Conclusion Patients with high-risk prostate cancer undergoing preoperative staging with 18F-NaF PET did not display a lower risk of developing SREs after prostatectomy compared with patients undergoing bone scintigraphy. The survival rates were similar between the two groups.